Development of a Collaborative Network Model to Develop a Healthy City in Local Government Organizations in Health Region 4 - Seangdao, Prachuab; Pookeaw, Chachanun; Pornpirin , Pornpirin; Kumnonoi, Patcharee (Ph.D. in Social Sciences Journal, 2026)
This research article aimed to (1) analyze problems and obstacles in developing Healthy Cities within local government organizations, (2) develop and implement a collaborative network model for Healthy City development, and (3) evaluate the outcomes of the model. A Research and Development (R&D) design was employed in four phases. Phase 1 studied the current situation and analyzed baseline data with 78 participants from six organizations. Phase 2 involved designing and validating the model with five experts. Phase 3 piloted the model with 90 participants from 30 local government organizations. Phase 4 evaluated outcomes using Healthy City assessment criteria. Instruments included in-depth interviews, questionnaires, and the Healthy City assessment form. Findings revealed major obstacles such as lack of inter-agency integration, policy discontinuity, limited budget, and insufficient public participation. The developed model consisted of eight components: raising awareness, defining network structure, knowledge exchange, resource integration, monitoring and evaluation, motivational mechanisms, communication, and capacity building. After implementation, the proportion of organizations meeting Healthy City standards increased from 5.0% to 66.7%. Public satisfaction and participation levels also improved significantly. In conclusion, the collaborative network model demonstrates strong potential for replication in other areas and serves as a practical framework to guide sustainable Healthy City development.